Ten year clinical evaluation of Starr-Edwards 2400 and 1260 aortic valve prostheses. Issue 4 (April 1987) - Hackett, D; Fessatidis, I; Sapsford, R; Oakley, C
Abstract : The long term performance characteristics of the 2400 and 1260 series of Starr-Edwards aortic prostheses were investigated by a follow up study of clinical outcome of 327 patients discharged from hospital with isolated aortic valve replacement. Follow up lasted for up to 10 years and was based on 1616 patient-years. The 2400 series cloth covered tracked valve was implanted in 182 patients from 1974 to 1980 and the 1260 series bare strut silastic ball valve was inserted in 145 patients from 1979 to 1983. Total 10 year mortality and valve related morbidity were low and no cases of mechanical valve failure were recorded. There were no significant actuarial differences in mortality or valve related morbidity between the 2400 and 1260 valves. Starr-Edwards models 2400 and 1260 aortic valve prostheses showed excellent durability without any mechanical failures over a 10 year period. The long term outcome of isolated aortic valve replacement with these models is associated with a low frequency of valve related complications.